Exploring the role of sustainability reporting strategies in promoting sustainable development in social economy entities: The circular economy as a mediator - Gallardo‐Vázquez, D.; Paiva, I. C. de S.; Nuevo‐Gallardo, C. (Sustainable Development, 2025)
This study focused on the relationship between sustainability reporting (SR), the circular economy (CE), and the United Nations' Sustainable Development Goals (SDGs), including an examination of the mediator role of the CE in the SR–SDGs relationship. The SR concept refers to the ways in which companies communicate with their internal and external stakeholders about their sustainability initiatives. Researchers have confirmed that the CE contributes to the achievement of SDGs based on SR. However, the literature does not offer any comprehensive frameworks that integrate these three concepts, which constitutes an important research gap. More specifically, very few studies have explored how social economy entities (SEEs) report the ways they contribute to achieving the SDGs while implementing CE practices. This research thus sought to make a significant contribution to filling this lacuna. Statistical analyses were conducted to determine how SR influences SDGs and how SR promotes these goals through the CE. Variance-based structural equation modeling via partial least squares was applied to process data on a sample of 90 SEEs in Spain. The results show that entities that provide sufficient SR often communicate how they are implementing SDGs. CE practices have a significant effect on this SR–SDGs relationship. The findings thus make an important contribution to the literature by exploring the link between these three strategies (i.e., SR, the SDGs, and the CE) in organizational contexts and thus providing a foundation for new business models.